Optimal dose of resistance training to improve handgrip strength in older adults with sarcopenia: a systematic review and Bayesian model-based network meta-analysis - Li Hua-Rui; Huang Shouliang; Yv Zhengze; Jiang Ning; Li Peihua; Zhai Yifei; Peng Fenglin (Frontiers in Physiology)
BackgroundSarcopenia is prevalent in older adults and affects their quality of life and overall health, low handgrip strength is one of the main manifestations of sarcopenia. Resistance training is an effective intervention for improving muscle strength in older adults, but the optimal dose of resistance training remains unclear. Therefore, the aim of this meta-analysis was to investigate the dose-response relationship between different doses of resistance training and grip strength in older adults.MethodsThis systematic review and network meta-analysis included a search in PubMed, Embase, and the Cochrane Library for randomized controlled trials from inception to 19 October 2024 of resistance training for patients with senile sarcopenia. Comprehensive data extraction covered dose, resistance training protocol, demographics, and study duration. Systematic review with Bayesian network meta-analysis (NMA) methodology was employed and results were presented as 95% credible intervals (Crl).ResultsA total of 13 studies involving 711 participants (mean age: 68.29 ± 5.30 years; mean BMI: 24.03 ± 3.43; female: 79.5%) were included in this study. The results of our network meta-analysis showed that resistance training variables (e.g., frequency, intensity, period, and training volume) were effective in improving handgrip strength in older patients with sarcopenia. Among them, the effective dose range for frequency of resistance training was 2–5 times/week, resistance training intensity was 30%–75%, resistance training period was 4–24 weeks, resistance training exercise was 3–17 exercises per set, resistance training repetitions was 10–24 reps, resistance training sets was 2–8 sets, resistance training volume was 528–2,200 reps per week. The optimal dose of resistance training to improve handgrip strength in older adults with sarcopenia is 3 times per week (MD = 7.02, 95% CrI [4.62, 9.42]), 49% 1RM (MD = 7.11, 95% CrI [2.69, 11.52]), 19 weeks (MD = 7.87, 95% CrI [3.89, 11.85]), 15 exercises (MD = 8.16, 95% CrI [3.65, 12.66]), 16 reps (MD = 7.62; 95% CrI [4.77, 10.46]), 6 sets (MD = 8.63; 95% CrI [5.06, 12.21]), 1,400 reps/week (MD = 8.45; 95% CrI [5.50, 11.40]).ConclusionResistance training effectively improves handgrip strength in older adults with sarcopenia. A recommended 19-week program includes 3 sessions per week at 49% 1RM, featuring 15 exercises per set, 6 sets, and 16 repetitions per exercise, totaling up to 1,400 reps weekly.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/recorddashboard.